Scaled boundary finite element method for fluid-structure interaction - Li, Shangming (2008)
This study presents the first attempt to extend the scaled boundary finite element method (SBFEM) for Fluid-Structure-Interaction problems. A fluid velocity-to-pressure relationship based on the SBFEM and acoustic approximations is developed. A FEM/SBFEM coupling procedure is presented. A new SBFEM formulation which involves a zero matrix for reservoir with absorptive flat bottom is derived.